Breastfeeding, adequate weight and a healthy lifestyle as preventive factors for breast cancer and recognition of some risk factors: La lactancia materna, peso adecuado y un estilo de vida saludable como factores preventivos para cáncer de mama y reconocimiento de algunos factores de riesgo - Silva-Sagastegui, Greysa Dianet (2024)
Cancer is a global health problem. When this pathology originates in the breast, a process occurs where healthy cells degenerate and become tumor cells. These cells proliferate to form tumors that can metastasize and cause significant damage to the body. Given the high incidence in our country, it was considered important to give more visibility to those factors that can protect women, who are significantly vulnerable, from developing this pathology. Through an exhaustive review of current scientific sources, it has been possible to identify those daily habits or practices that protect or reduce the risk of developing a malignant neoplasia in the breasts and at the same time those factors that can be modified or prevented have been recognized as they predispose to the population to a small or large extent to develop the disease. This will simultaneously provide a clear and updated vision of the topic to health professionals, to take action in the future and reinforce health promotion.